Ask a New Question
Search
lim x->0 sinx secx /
Prove the following:
[1+sinx]/[1+cscx]=tanx/secx =[1+sinx]/[1+1/sinx] =[1+sinx]/[(sinx+1)/sinx] =[1+sinx]*[sinx/(sinx+1)]
3 answers
asked by
Anonymous
917 views
My previous question:
Verify that (secx/sinx)*(cotx/cscx)=cscx is an identity. (secx/sinx)*(cotx/cscx) = (secx/cscx)(cotx/sinx) =
2 answers
asked by
Jon
896 views
how do i simplify (secx - cosx) / sinx?
i tried splitting the numerator up so that i had (secx / sinx) - (cosx / sinx) and then i
1 answer
asked by
v
5,719 views
Simplify (1+tanx)^2
The answer is (1-sinx)(1+sinx) Here's what I do: 1 + 2tanx + tan^2x When I simplify it becomes 1 +
1 answer
asked by
AlphaPrimes
637 views
1/tanx-secx+ 1/tanx+secx=-2tanx
so this is what I did: =tanx+secx+tanx-secx =(sinx/cosx)+ (1/cosx)+(sinx/cosx)-(1/cosx)
0 answers
asked by
olivia
1,308 views
Complete the following identity secx-1/secx=? I have four multiple choice options and can't seem to work my way to either one.
3 answers
asked by
Anne
745 views
Trigonometric Identities
Prove: (tanx + secx -1)/(tanx - secx + 1)= tanx + secx My work so far: (sinx/cosx + 1/cosx +
0 answers
asked by
Dave
1,424 views
I'm working this problem:
∫ [1-tan^2 (x)] / [sec^2 (x)] dx ∫(1/secx)-[(sin^2x/cos^2x)/(1/cosx) ∫cosx-sinx(sinx/cosx)
1 answer
asked by
Janice
676 views
tanx+secx=2cosx
(sinx/cosx)+ (1/cosx)=2cosx (sinx+1)/cosx =2cosx multiplying both sides by cosx sinx + 1 =2cos^2x sinx+1 =
0 answers
asked by
shan
958 views
1. (sinx/cscx)+(cosx/secx)=1
2. (1/sinxcosx)-(cosx/sinx)=tanx 3. (1/1+cos s)=csc^2 s-csc s cot s 4.
1 answer
asked by
Tom
739 views